HUBUNGAN PENGGUNAAN CHATGPT DENGAN LITERASI DIGITAL MAHASISWA TEKNOLOGI PENDIDIKAN UNIVERSITAS NEGERI PADANG - Marnita, Selfi Marnita; Anugrah, Septriyan; Hendri, Nofri; Yusri, Meldi Ade Kurnia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study investigates the relationship between ChatGPT usage and digital literacy among students of the Educational Technology Study Program at Universitas Negeri Padang (UNP). Preliminary observations found that 97% of students actively use AI tools predominantly ChatGPT yet critical evaluation of AI-generated content remains limited. A quantitative correlational design was employed with a population of 611 active students (cohorts 2020–2025); 242 respondents were selected via proportional random sampling (Slovin’s formula, 5% error margin). ChatGPT usage was measured across three indicators (Use Skill, Critical Understanding, Communicative Ability) and digital literacy across eight DigComp 2.1 dimensions. Data were analysed using Microsoft Excel 2019 and SPSS 27; non-normality (Kolmogorov Smirnov: Asymp. Sig. = 0.006 < 0.05) warranted Spearman Rank correlation. Results show ChatGPT usage at a moderate level (mean = 49.20 of 60; 69.0%) and digital literacy similarly moderate (mean = 67.00 of 80; 70.7%). The Spearman coefficient (rs = 0.750; p < 0.001) confirms a strong, significant positive relationship between the two variables.